The role of descending basal ganglia connections to the brain stem in parkinsonian akinesia. - Aziz, T; Davies, L; Stein, J; France, S (1998)
Akinesia is the most disabling symptom of Parkinson's disease. The neural mechanisms underlying it probably involve the descending projections of the basal ganglia to the brain stem as it improves after a pallidotomy or subthalamic nucleotomy but not after a thalamotomy. We describe the effects of lesioning the pedunculopontine nucleus in the normal primate in generating an akinetic syndrome. The possible clinical implications of this study are discussed.